Fuzzy control of robotic manipulators - Er, Meng J.; Mastorakis, Nikos E. (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an Intelligent Control Strategy for an n-degree-of-freedom (d.o.f.) robotic manipulator. It covers the design and simulation study of a Fuzzy Controller (FC) for the robotic manipulator with a view of tracking a predetermined trajectory of motion in the joint space. An industrial robotic manipulator, Adept One Robot, was used to evaluate the effectiveness of the proposed scheme.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka